VALUE INCREASING ELECTRONIC COMMERCE SOLUTIONS IN THE APPAREL INDSUTRY - Kathleen DiIorio; June Wei (Issues in Information Systems, 2011)
EVA has recently been touted by the business press, analysts and researchers as the best method for assessing firm performance. EVA focuses on maximization of incremental income above capital costs while adjusting for accounting items frequently used to manager earnings. In the current study, EVA is used to assess differences in firm performance as related to IT investment in order to add charity to conflicting results in the extant research. Our study focuses on manufacturing firms during 1998-2000 when there was widespread adoption of factory automation, enterprise resource planning and advanced production scheduling systems. Consistent with several earlier studies, results in the sample firms were inconsistent when applying traditional accounting measures (i.e., IT investment was not correlated with increases in ROI and ROA but was correlated with ROE and ROS). However, a significant relationship exists between IT investment and EVA, indicating increased IT investment was associated with increased wealth creation.